The Phenomenon of the Secularization of Canon Law as an Epistemological Issue - Michowicz, Przemysław (Prawo Kanoniczne, 2026)
The author advances an epistemological reinterpretation of the secularization of canon law that moves beyond prevailing sociological and institutional approaches. The central claim is that contemporary transformations of the canonical normative order–most notably the increasing reception of solutions developed within secular legal systems–cannot be adequately explained without a systematic analysis of the conditions of knowability, justification, and rational legitimation of the Church’s legal norms. Conceived as an epistemic category, secularization discloses a constitutive tension between the theological grounding of canon law and its historical, cultural, and institutional actualization. The inquiry is situated at the intersection of legal epistemology, the philosophy of canon law, and theology, highlighting the distinctive character of legal cognition, which operates not only with claims to certain knowledge but also with normatively justified beliefs embedded within specific paradigms of rationality. From this perspective, secularization emerges as a mechanism of epistemic shift: from the immediate appeal to the authority of the sacred toward mediated forms of normative justification grounded in practical reason, procedural rationality, and systemic coherence. A diachronic analysis further demonstrates that the canonical legal order has, from its inception, developed in sustained dialogue with dominant models of legal rationality, remaining receptive to secular institutions and normative techniques–thereby precluding any notion of its epistemic isolation.